Strategi Pemasaran Bisnis Travel Umroh Menggunakan Analisis SWOT (Studi Kasus PT. Hamdan Syakuro Alkhoir) - Nazura, Is Anin; Sihombing, Rustam (Universitas Mercu Buana, 2024)
This research is motivated by the increasingly rapid development of Muslims in the world and in Indonesia in particular. One of the pillars of Islam is the Hajj. If you can afford it, to get to Mecca you need a means of transportation. With good means of transportation, pilgrims can carry out the Hajj and Umrah pilgrimages safely, calmly and without any hassle. This research aims to determine the strengths, weaknesses, opportunities and threats (Strengths, Weakness, Opportunities and Threats) faced, as well as the appropriate marketing strategy to be implemented at PT. Hamdan Syakuro Alkhoir. This research uses a qualitative approach, where field data collection is carried out using interviews and document searches. From the research results that have been explained, it can be concluded that the SWOT analysis of PT. Hamdan Syakuro Alkhoir is guaranteed with a score of 0.4, while the weakness is the limited number of people responsible for distribution (lack of employees) with a score of 0.3. Second SWOT analysis of PT. Hamdan Syakuro Alkhoir regarding external factors for opportunities is the existence of good service with a score of 0.15, while the threat is the existence of competition between the same bureaus with a score of 0.04. The final result is the position of PT. Hamdan Syakuro Alkhoir is currently in quadrant I, namely growth strategy. This result is determined based on the average score on IFAS 2.4 and EFAS 3.31, so that the best alternative strategy for business development, especially the marketing strategy of PT. Hamdan Syakuro Alkhoir with a strength opportunities (SO) strategy is to maintain and improve service quality so that it can increase the opportunities that will be obtained by PT. Hamdan Syakuro Alkhoir. Based on the research conclusions, the author recommends in the form of suggestions, namely, PT. Hamdan Syakuro Alkhoir should implement a growth strategy by maintaining and improving the quality of services at PT. Hamdan Syakuro Alkhoir. Then the identification of strategies from researchers can be included as a strategic consideration for promotion of various service sectors in general in Hajj and Umrah travel services, and especially in PT. Hamdan Syakuro Alkhoir. Apart from being able to increase the value of the PT brand. Hamdan Syakuro Alkhoir, can also strengthen vision. Hamdan Syakuro Alkhoiry is to prioritize service and create comfort and uniqueness for the congregation in worship.